China is a Key to Mitigate Global Climate Change - Beche bt Mamma (Andalas Journal of International Studies (AJIS))
This paper attempts to discuss China’s response on the global climate change. China, well known as the world’s largest emitter of greenhouse gases, the largest energy consumer and the second largest economy in the world, contributes for a third of the planet’s greenhouse gas output and has one of the world’s most polluted cities that surpassed United States and India. China’s economy growth has changed its perception on how they should cultivate their land, water, and natural resources. This economic expansion which is driven by fossil fuels, has led to dramatic increases in emissions of greenhouse gases (GHGs). The world concerns on environmental problems in China because it influences the world whether pattern, it effects human life and it influences global community market. Keywords: Greenhouse Gases, Environmental Problems, Economy Growth